Development and validation of a general legal moral disengagement scale - Kirshenbaum, Jacqueline M. (Psychology, crime & law, 2021)
Current moral disengagement (MD) scales are insufficient for measuring MD in general legal contexts. We created a general legal MD scale measuring moral disengagement from both minor and serious crime, and both one’s own and others’ immoral behavior. We conducted both an exploratory and confirmatory factor analysis, which resulted in five factors: (1) authoritarian punishment, (2) personal minor transgressions, (3) harm minimization, (4) euphemistic labeling, and (5) dehumanization. Supporting convergent validity, the scale related to four other MD scales that pertain to either general or specific legal contexts (e.g. the execution process). Supporting divergent validity, the scale was unrelated to political locus of control. The scale also significantly and predictably related to several individual differences including social dominance orientation, legal authoritarianism, attributional complexity, and just world beliefs. Last, the new MD scale predicted legal attitudes that moral disengagement should be related to. Specifically, the new MD scale predicted attitudes toward controversial police procedures (i.e. controversial warrants and interrogation techniques) and policies (e.g., immigrant ban).